2001
DOI: 10.1074/jbc.m006760200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Human Prothrombin by Arginine-specific Cysteine Proteinases (Gingipains R) from Porphyromonas gingivalis *

Abstract: The effect of 95-(HRgpA) and 50-kDa gingipain R (RgpB), arginine-specific cysteine proteinases from periodontopathogenic bacterium Porphyromonas gingivalis on human prothrombin activation was investigated. Each enzyme released thrombin from prothrombin in a dose-and time-dependent manner with the former enzyme, containing adhesion domains, being 17-fold more efficient than the single chain RgpB. A close correlation between the generation of fibrinogen clotting activity and amidolytic activity indicated that ␣-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 48 publications
(43 reference statements)
3
55
0
Order By: Relevance
“…Activation of pro-u-PA by a bacterial protease has not been reported previously, and the activation of factor X, prothrombin, and protein C has recently been demonstrated by arginine-specific cysteine proteases (gingipains) from Porphyromonas gingivalis, a causative bacterium of periodontitis (33)(34)(35). Proteases from foreign sources are thought to be virulence factors involved in inflammatory events occurring at infected sites, where fibrin deposition is a common feature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of pro-u-PA by a bacterial protease has not been reported previously, and the activation of factor X, prothrombin, and protein C has recently been demonstrated by arginine-specific cysteine proteases (gingipains) from Porphyromonas gingivalis, a causative bacterium of periodontitis (33)(34)(35). Proteases from foreign sources are thought to be virulence factors involved in inflammatory events occurring at infected sites, where fibrin deposition is a common feature.…”
Section: Discussionmentioning
confidence: 99%
“…7, A and B). The cleavage occurred at Asp 34 -Leu 35 and Arg 52 -Ile 53 of the heavy chain (Fig. 7, C and D).…”
Section: Fig 3 Characterization Of Plasminogen Cleavage By Bl-mamentioning
confidence: 99%
“…As a matter of fact, studies have shown that P. gingivalis Arg-gingipains are able to activate prothrombin and coagulation factor X. 39,40 Interestingly, PAR 2 has been described as the endogenous receptor mediating the effects of factor Xa in endothelial cells. 41 Therefore, P. gingivalis Arg-gingipains could account for PAR 2 activation both directly (by cleaving the receptor) and indirectly (by inducing the release of PAR 2 -activating proteases).…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting of human brain supernatant using anti-prothrombin (1:20,000; Dako Corp., Glostrup, Denmark) and anti-human thrombin (0.5 g/ml; American Diagnostica Inc., Stamford, CT) antibodies showed bands corresponding to prothrombin, prethrombin-1, prethrombin-2, the B chain of ␣-thrombin, and the B2 chain of ␤-thrombin ( Fig. 2) (22). Fig.…”
Section: Effect Of Ppack On the Breakdown Of Endogenous Tau In Solublmentioning
confidence: 99%